Allelopathic Effects of Litter Axonopus compressus against Two Weedy Species and Its Persistence in Soil. (23rd October 2013) - Samedani, B.; Juraimi, A. S.; Rafii, M. Y.; Anuar, A. R.; Sheikh Awadz, S. A.; Anwar, M. P.
Abstract : This study investigated the allelopathic effect of Axonopus compressus litter on Asystasia gangetica and Pennisetum polystachion . In experiment 1 the bioassays with 0, 10, 30, and 50 g L −1 of aqueous A. compressus litter leachate were conducted. Experiment 2 was carried out by incorporating 0, 10, 20, 30, 40, and 50 g L −1 of A. compressus litter leachate into soil. In experiment 3, the fate of A. compressus litter leachate phenolics in the soil was investigated. A. compressus leachates did not affect the germination percentage of A. gangetica and P. polystachion, but delayed germination of A. gangetica seeds and decreased seed germination time of P. polystachion . A. compressus litter leachates affected weeds hypocotyl length. Hypocotyl length reductions of 18 and 31% were observed at the highest concentration (50 g L −1 ) compared to the control in A. gangetica and P. polystachion, respectively. When concentration of A. compressus litter leachate-amended soil increased A. gangetica and P. polystachion seedling shoot length, root length, seedling weight and chlorophyll concentration were not affected. The 5-week decomposition study of A. compressus showed that the phenolic compounds in A. compressus litter abruptly decreased about 52% after two weeks and remained steady until the end of the incubation.